2010
DOI: 10.1177/1757913910384050
|View full text |Cite
|
Sign up to set email alerts
|

Arts on Prescription: A review of practice in the UK

Abstract: The current levels of psychosocial distress in society are significant, as evidenced by the number of prescribed antidepressants and the numbers of working days lost as a result of stress and anxiety. There is a growing body of evidence that active involvement in creative activities provides a wide range of benefits, including the promotion of well-being, quality of life, health and social capital. In the U.K. there are currently a number of projects operating that offer Arts on Prescription for people experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 11 publications
1
116
0
9
Order By: Relevance
“…Small-scale choral studies with PD have shown improvements in QOL [40], speech intelligibility [41], breath control, and prosody [42]. Large-scale studies of choir participation with healthy older adults indicate improved QOL [43,44], social engagement [45,46], mood [47], immune functioning [48], and overall health [49].…”
Section: Choral Singing Therapy As a New Approach To Enhance Living Wmentioning
confidence: 99%
“…Small-scale choral studies with PD have shown improvements in QOL [40], speech intelligibility [41], breath control, and prosody [42]. Large-scale studies of choir participation with healthy older adults indicate improved QOL [43,44], social engagement [45,46], mood [47], immune functioning [48], and overall health [49].…”
Section: Choral Singing Therapy As a New Approach To Enhance Living Wmentioning
confidence: 99%
“…6,3 Further benefits of art-making include increased positive affect, self-esteem, and improved social skills and working memory. 1,6,7,8,9 Various models have been proposed to explain why and how participatory arts may improve wellbeing. 10 For example, early models to explain the effects of expressive writing on wellbeing proposed that art enables catharsis, whereby disclosing once inhibited affective content reduces stress and improves immune system functioning.…”
Section: Introductionmentioning
confidence: 99%
“…It improves well-being of patients in palliative and oncological care, and also supports clinical work with patients with mental disorders [26]. In the U.K. there is currently a number of projects operating that offer Arts on Prescription designed for people with mental health problems and experiencing social isolation aiming at helping people in their recovery through creativity and increasing their social engagement [27].…”
Section: Visual Art As Medication -Research Reviewmentioning
confidence: 99%